Microbiological Impact Assessment of Air Environment of the Hides and Skin Processing Unit of NILEST Tannery, Zaria - J. O. Oko; Regina Abua (Archives of Current Research International, 2016)
Introduction: Microbial analysis of air is one of the most vital investigations of determining the microbial air pollution. The information on the microbial concentration of bacteria and fungi is necessary both to estimate the health hazard and to create standard for air quality control. Aim: This study was carried out to investigate the microbiological quality of the air environment in the hides and skin processing unit of NILEST Tannery, Zaria. Methodology: The analysis was carried out using the settle-plate method. The plates were exposed during passive and active sessions for 30 to 60 minutes. Results: The bacteria isolated and identified include Proteus mirablis, Pseudomonas aeruginosa, Salmonella enterica, Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniawhereas the fungi isolated include Sclerotium sp., Fusarium sp., Aspergillus niger, Aspergillus fumigatus, Corticium sp., and Aspergillus ficheri. The mean total bacteria load recorded during passive and active sessions were 180 cfu/m3 and 254 cfu/m3 respectively. Those of fungi were 115 cfu/m3 and 284 cfu/m3respectively. Conclusions: The isolation of these microorganisms from the study area is indicative of workers being exposed to potential bio-hazards and therefore there is the need for adequate measures to reduce the risk of exposure to pathogenic strains.